Early lessons from the implementation of universal respiratory syncytial virus prophylaxis in infants with long-acting monoclonal antibodies, Galicia, Spain, September and October 2023 - Martinón-Torres, Federico; Mirás-Carballal, Susana; Durán-Parrondo, Carmen (Euro surveillance : bulletin européen sur les maladies transmissibles, 2023)
A monoclonal antibody for universal respiratory syncytial virus prophylaxis in infants has recently been licensed. We share our experiences of integrating nirsevimab into the regional immunisation programme in Galicia, Spain. After a 3-week hospital-based immunisation campaign with flexible individualised appointments and educational activities, nirsevimab uptake was 97.5% in the high-risk group, 81.4% in the catch-up group and 92.6% in infants born during the campaign. This successful implementation strategy can serve as a model and may inform other countries’ programmatic deliberations.